Job perception and expectations scale: a new scale for assessing self-perceived employability, job quality, and gender equity - Pepa López; Pep Simó; Jordi Marco (Humanities & Social Sciences Communications)
Abstract Numerous studies have identified career prospects as a key determinant in students’ decisions to pursue a STEM degree. The challenge lies in understanding the perceptions and expectations of the new generations regarding Career Prospects in a given field. To address this, the present study proposes a new scale focused on analyzing the perception of employability and expectations of job quality in the field, using the most commonly considered elements in the literature. Gender equity, or the lack thereof, is also related to job satisfaction for some individuals. Therefore, it has also been included in the analysis to better assess its differential impact across genders. The scale evaluates four dimensions: generic employability, sector-specific employability, gender equity, and job quality. In this study, a 27-item scale was designed to measure self-perceived employability both in a generic and sector-specific way, the perception of gender equity and expectations regarding job quality in the field. This questionnaire was completed by 305 first-year engineering students at a Catalan university (75 identifying as female), with an average age of 18.3 years (SD 1.1). During the study, 25 out of the 27 items were retained. High reliability and differentiation were observed for the four dimensions of the scale. The indicators of the confirmatory factor analysis suggest a reasonable fit and a robust construct validity. We believe the developed scale has significant potential to assess students’ perceptions and expectations regarding employment in a field. This scale can be used as a diagnostic tool, especially for planners. For example, it could be used to analyze gender differences in perceptions and expectations within a field, or the relationship between these perceptions and the choice of university studies. This analysis could allow corrective actions to be taken in response to unrealistic perceptions and expectations, should this be the case.